Flood Detection Design based on the Internet of Things - Silaban, Freddy Artadima; Taufiq, Yufimar; Silalahi, Lukman Medriavin; Sihombing, Grace Lamudur Arta (Buletin Ilmiah Sarjana Teknik Elektro, 2023)
Flood detection devices and water levels from several previous research studies were not optimal because they were still running and manual information, such as through loudspeakers, in some research, electronic devices have been used, but no information has been obtained, and it is not optimal if there is a danger sign. So this research is a study on the development of an automatic flood detection system and water level based on the IoT (Internet of Things). The system uses a NodeMCU Esp8266 controller with a combination of potentiometer sensors mounted on a water-level mechanic and connected to the Thingspeak IoT platform. Based on the results of the analysis and testing that have been done, the system is designed to combine the previous research algorithms so that it works more optimally and is better. The flood detection system and water level are made in two parts: one is placed upstream and the other is placed downstream, where the devices are connected. The device will turn on a danger alert when the altitude percentage is more than 85% of the maximum height. The lag time in the upload and download process is included in the Fast category (≤10 seconds). The resulting information can be monitored through the media portal website.